Islamic Capital/Anatolian Tigers: Past and Present - Hosgor, Evren (Routledge Journals, Taylor & Francis Ltd, 2011)
This article critically reviews the current literature on 'Islamic capital' in Turkey. Instead of a culturalist account that primarily focuses on conservative lifestyles and religious orientations of entrepreneurs as the main indicator of class formation, it tries to identify a criterion on which 'Islamic capital' as such can be identified as a separate capital fraction that can pursue a distinct and collective agenda. It discusses the symbiotic relationship between interest-free banks, firms, religious networks and communal linkages in order to understand this peculiar way of capital accumulation in relation to Islamic motifs. It also provides guidelines to understand what the future may hold for this specific capital fraction and assess the explanatory capacity of the term 'Islamic capital' under present conditions.